Jessica's secret love - William, Kate.; Pascal, Francine; Copyright Paperback Collection (Library of Congress) (New York : Bantam Books, 1994)
Falling hopelessly in love with Jeremy Randall, Jessica believes he is everything she ever dreamed of and is devastated when he ends their relationship, until she learns that he is already engaged to marry her friend and houseguest, Sue.
"A Bantam book"--T.p. verso.
Keywords: Love stories; Love stories; Young adult fiction